Analysis of Principal Managerial Competencies in Sub School Planning at Petualang Pantai Elementary School - Elfira, Elfira; Nurochmah, Andi; Mus, Sumarlin (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2024)
School principals are required to have managerial competence where school principals are required to be able to prepare short-term, medium-term and long-term plans. This research analyzes the preparation process annual work plan , budget plan and strategic plan. This research was conducted using analysis with a qualitative descriptive research type. First, the results of research on the process of preparing strategic plans found that the school's vision, mission, goals and strategies were not formulated because the principal only continuing the vision, mission, goals and strategies of the previous principal. Second, the process of preparing the annual work plan has not been implemented optimally because a drafting team was not formed, and a situational analysis was not carried out. This is reinforced by the fact that no documents were found in the preparation process. Third, the process of preparing the school budget work plan involves the principal and school treasurer and principal without holding meetings with teachers, staff, committees and school supervisors. Interviews, observation and documentation are the data collection techniques used. The Miles and Huberman model is a technique used in data analysis.